New Records of Fungi on Wheat Grains From Iraq - Abdullah, Samir KH.; Mohammad Atrosh, Halben I. (Science Journal of University of Zakho, 2014)
The present study recorded eight fungal species on wheat grains for the first time in Iraq. These included Arthrinium phaeospermum, Bipolaris sorokiniana, B.spicifera, Chaetomium elatum, Emericella rugulosa, Eurotium herbariorum Nigrospora state of Khuskia oryzae and Ulocladium alternariae. Brief descriptions with photographs are provided for the newly recorded species.